Equine gestational length and location: is there more that the research could be telling us?. Issue 12 (28th November 2017) - Clothier, J; Hinch, G; Brown, W; Small, A
Abstract : Clear definitions of 'normal' equine gestation length (GL) are elusive, with GL being subject to a considerable number of internal and external variables that have confounded interpretation and estimation of GL for over 50 years. Consequently, the mean GL of 340 days first established by Rossdale in 1967 for Thoroughbred horses in northern Europe continues to be the benchmark value referenced by veterinarians, breeders and researchers worldwide. Application of a 95% confidence limit to reported GL range values indicates a possible connection between geographic location and GL. Improved knowledge of this variable may help in assessing the degree of the neonate's prematurity and dysmaturity at or soon after birth, and identification of conditions such as incomplete ossification of the carpal and tarsal bones. Associated pathologies such as bone malformation and fracture, angular limb deformity and degenerative joint disease can cause chronic unsoundness, rendering horses unsuitable for athletic purpose and shortening ridden careers. This review will examine both the factors contributing to GL variation and the published data to determine whether there is potential to refine our understanding of GL by establishing a more accurate and regionally relevant GL range based on a 95% confidence limit. This may benefit both equine industry economics and equine welfare by improving early identification of skeletally immature neonates, so that appropriate intervention may be considered.